Development of strategies for improving Buton asphalt delivery services at the Nambo Port Buton regency - Rachman, Andi Imam Arief; Wicaksono, Achmad; Wicaksono, Agus Dwi (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the performance of port operational services, and formulate priority strategies to improve the performance of asphalt distribution services. It is focuses on Nambo Port, which has an important role in the distribution of Buton asphalt to various regions. The study aims to improve the operational efficiency and quality of asphalt delivery services at Nambo Port. Previous studies mentioned that the performance of asphalt loading and unloading at Nambo Port is not good. Therefore, to overcome the problem, this study tries to complement the previous study by applying the Kano model to evaluate and improve the service quality of Buton asphalt distribution at Nambo Port. The main findings show that the ratio of effective loading and unloading time and mooring time of ships reached 63,75 %, which are at least 70 %. In addition, the unloading rate of asphalt is 37,26 tons/hour, which are at least 100 tons/hour. These results show that ships spend a lot of time loading and unloading asphalt at the dock. Through the prioritized strategies generated from the Kano model, it is possible to address the identified problems. The resulting strategies emphasize the efficiency of loading and unloading operations, heavy equipment readiness, expedition fleet readiness, fast and transparent administrative processes, and management of port facility infrastructure such as lighting, road conditions, and security. The proposed strategy can be applied in practice with infrastructure development, effective coordination between stakeholders, and monitoring of operations to ensure sustainability of improvements. Thus, the implementation of these strategies is expected to improve the performance of efficient